Positive Parenting Impact on Parenting Patterns and Attachment Between Parents and Children - Ineu Maryani; Yusi Riksa Yustiana (Balai Diklat Keagamaan Bandung, 2026)
Abstrak:Studi ini bertujuan untuk menganalisis dampak pengasuhan positif terhadap keterikatan antara orang tua dan anak di SMPN 1 Cik This study aims to analyze the impact of positive parenting on the attachment between parents and children at SMPN 1 Cikalongwetan. A total of 1,021 parents/guardians participated as respondents, with a 68% attendance rate in the parenting program. Data were collected through closed- and open-ended questionnaires and analyzed using descriptive statistics and thematic analysis. The findings show that 78.3% of parents considered the parenting program very important, 19.7% assessed it as fairly important, and only 2% reported “don’t know.” Identified impacts include increased knowledge of adolescent development, adjustments in parenting practices based on children’s needs, strengthened emotional attachment, enhanced supervision of peer interactions, active learning support, reinforcement of moral and religious values, and agreement on gadget use. Moreover, 52% of respondents recommended implementing the program every semester. These findings reinforce the literature on positive parenting as a protective factor against juvenile delinquency and character formation. Parenting programs prove to be relevant as a collaborative strategy between schools and families in fostering a resilient young generation. alongwetan. Sebanyak 1.021 orang tua/wali berpartisipasi sebagai responden, dengan tingkat kehadiran 68% dalam program pengasuhan. Data dikumpulkan melalui kuesioner tertutup dan terbuka dan dianalisis menggunakan statistik deskriptif dan analisis tematik. Hasil penelitian menunjukkan bahwa 78,3% orang tua menganggap program pengasuhan sangat penting, 19,7% menilai cukup penting, dan hanya 2% yang menyatakan “tidak tahu”. Dampak yang teridentifikasi meliputi peningkatan pengetahuan tentang perkembangan remaja, penyesuaian praktik pengasuhan berdasarkan kebutuhan anak, penguatan keterikatan emosional, peningkatan pengawasan interaksi antar teman sebaya, dukungan pembelajaran aktif, penguatan nilai-nilai moral dan agama, dan kesepakatan tentang penggunaan gadget. Selain itu, 52% responden merekomendasikan penerapan program setiap semester. Temuan ini memperkuat literatur tentang pengasuhan positif sebagai faktor pelindung terhadap kenakalan remaja dan pembentukan karakter. Program pengasuhan terbukti relevan sebagai strategi kolaboratif antara sekolah dan keluarga dalam membina generasi muda yang tangguh.Kata kunci: pengasuhan positif; keterikatan; orang tua; anak-anak